PERAN NEGARA DALAM PERUMUSAN KEBIJAKAN PENGENDALIAN TERORISME DI INDONESIA (Study Analisa Kriminologis) - Rudy Rudolf Valentino (UIR PRESS, 2016)
The tragedy of Bali Bombing in Legian-Kuta in October 12, 2002 brought the issue of terrorism to the forefront of Indonesia’s security thinking. In Indonesia’s counter terrorism policy, terrorism is defined as criminal act. This has been a long debate due to the ambiguities in the definition of terror and has produced multi-interpretation. People anxious this definition of terror interpreted freely by stakeholders. As a result,the ideal purpose of a policy could not be achieved, on the contrary it will produce a new problem that harms democracy. This research concludes that the state has played an important role to formulate Indonesia’s counter terrorism strategy in Law Enforcement model in order to protect human rights in the democracy framework. However, this Law Enforcement model should be supported by the preventive measures which will be regulated under social policy to keep the coercive power and the persuasive power balance.